Introduction to the thematic feature: Deep and disruptive transformations: The new normal for organizations and their stakeholders - Ben Slimane, Karim; Kooli, Kaouther; Skandrani, Hamida; Khorana, Sangeeta (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
This paper introduces the special issue on the topic of the New Normal of Organizations. It begins by positioning the New Normal concept within the extensive literature in management, outlining central historical milestones in its emergence and its relationship to crises, including the COVID-19 pandemic in particular. Second, based on the insights derived from the four accepted papers and the recent debates in the literature, we construct three main contributions to management theory concerning the New Normal: the Normal as a proto-institution, the New Normal as an opportunity to rethink resilience, and the role of technology in crafting the New Normal.